Synergistic effect of a r-GO/PANI nanocomposite electrode based air working ionic actuator with a large actuation stroke and long-term durability1. Issue 16 (28th April 2015) - Liu, Qing; Liu, Luqi; Xie, Ke; Meng, Yuena; Wu, Haiping; Wang, Guorui; Dai, Zhaohe; Wei, Zhixiang; Zhang, Zhong
<x xml:space="preserve">Abstract</x> A r-GO/PANI nanocomposite based air working ionic actuator demonstrates a large actuation stroke and long-term durability.